Use Of Interactive Educational Methods in The University - Ergashev Jamshid Koldoshevich (Genius Journals, 2024)
This article discusses the difference between passive and active interactive teaching methods. The university offers various methods of interactive learning, which are used in lectures, seminars and laboratory exercises.
Keywords: interactive teaching method; passive form of education; brainstorming